Baseline Survey Report: I. Jungu, Dolakha. Integrating traditional crop genetic diversity into technology: using a biodiversity portfolio approach to buffer against unpredictable environmental change in the Nepal Himalayas - Pudasaini, N.; Sthapit, S.R.; Gauchan, D.; Bhandari, B.; Joshi, B.K.; Sthapit, B.R. (LI-BIRD, NARC and Bioversity International, 2016)
The project has set a mandate to work on eight neglected and underutilized mountain crops that are nutrient dense, climate resilient, and indigenous to the Nepal Mountains (Table 1). These crops are: amaranth (Amaranthus hypochondriacus, A. caudatus and A. cruentus), barley and naked barley (Hordeum vulgare and H. vulgare var. nudum), common bean (Phaseolus vulgaris), buckwheat (Fagopyrum esculentum and F. tataricum), finger millet (Eleusine coracana), foxtail millet (Setaria italica), proso millet (Panicum miliaceum) and cold tolerant rice (Oryza sativa).